Monetary policy, taxation, and international investment strategy - Canto, Victor A.; Laffer, Arthur B. (New York : Quorum Books, 1990)
The book attempts to illustrate how incentives and disincentives affect economic behavior and the performance of the economy. It also presents a top-down approach that shows how to trace the impact of government policies through the economy and thereby discover investment implications that will be helpful to investors and policy makers.
Includes bibliographical references and index.
nmn 22/05/13
Loans
Keywords: Monetary policy; Taxation; Investments, Foreign